Tuberculin skin test positivity among HIV infected alcohol drinkers on antiretrovirals in south-western Uganda - Muyindike, Winnie R.; Fatch, Robin; Cheng, Debbie M.; Emenyonu, Nneka I.; Ngabirano, Christine; Adong, Julian; Linas, Benjamin P.; Jacobson, Karen R.; Hahn, Judith A. (PLoS ONE, 2020)
Tuberculosis (TB) is the leading cause of death among people living with HIV (PLWH), and current evidence suggests that heavy alcohol users have an increased risk of developing TB disease compared to non-drinkers. Not known is whether the increased risk for TB disease among alcohol users may reflect higher rates of latent TB infection (LTBI) among this population. We assessed the latent TB infection prevalence based on tuberculin skin testing (TST) and examined association with current alcohol use among HIV-infected persons on antiretroviral therapy (ART) in south-western Uganda. We included PLWH at the Mbarara Regional Hospital HIV clinic, who were either current alcohol consumers (prior 3 months) or past year abstainers (2:1 enrolment ratio). Participants were recruited for a study of isoniazid preventive therapy for LTBI. TST was performed using 5 tuberculin units of purified protein derivative. The primary outcome was a positive TST reading (5mm induration), reflecting LTBI. We used logistic regression analyses to assess the cross-sectional association between self-reported current alcohol use and a positive TST.
Keywords: Tuberculin skin test; HIV infected; Alcohol drinkers; Antiretrovirals; South-western Uganda